If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -6 = 30 Reorder the terms: -6 + 3y = 30 Solving -6 + 3y = 30 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 3y = 30 + 6 Combine like terms: -6 + 6 = 0 0 + 3y = 30 + 6 3y = 30 + 6 Combine like terms: 30 + 6 = 36 3y = 36 Divide each side by '3'. y = 12 Simplifying y = 12
| 2x^3+3x^2-18x-8=0 | | (10y)+(3y+11)=180 | | 9=4y+5 | | 17x^2-52x+308.6=0 | | 17x^2-52x+308.6=n | | 7x-14=3-3x | | x-9x+8x-3x= | | y/3-3=-7 | | a^2-b^2=196 | | -1=x/6 | | .3+1x=.4(6+x) | | 2x-9=28 | | x^2+4i=0 | | (9+4)-(1-4)+3-5=14 | | 5h+11hk+9h+4hk= | | 5x^2-39+28=0 | | -9(x-5)+7=52 | | -1.8-x=9+2x | | 0.15x+220.00=319.00 | | -8-7=24 | | 8x+22=180 | | -4(3x-9)=30 | | -17-3/-5+7(-2) | | 5x^2-39-28=0 | | 6(7n)3= | | -2(9s-8)=28+4s | | -7(y+7)=-8y | | 0.4c+2.55=0.65 | | x^4+16x^3+39x^2=0 | | -1/2p=4 | | (8A)(5C)= | | 6x^2-216x+105=0 |